Espaços e tempos na educação infantil: quando os retalhos se unem - Rocha, Gabriele de Andrade (2018)
This dissertation has as theme spaces and times in Early Childhood Education. It is linked to the line of research Pedagogical Management and Educational Contexts of the Graduate Program in Public Policies and Educational Management (Professional Master's Degree) at Universidade Federal de Santa Maria (UFSM)-RS. The objective is to reflect on the relations between the organization and the use of spaces and times in Early Childhood Education through continuing teacher training. It has as a locus of research the Cycle of Studies organized by the Regional Forum of Early Childhood Education of the Central Region (FREICENTRAL), which took place at UFSM with teachers and managers of Early Childhood Education in the municipalities of the Central Region and later in an EMEI of the municipal public network of Santa Maria. The methodology is characterized by a qualitative nature, of the intervention research type (DAMIANI et al., 2013) and consisted in formative meetings with managers and teachers. The reflection was triggered by images of the spaces and times at Early Childhood Education institutions requested prior to the meetings, as well as theoretical references that problematize spaces and times in Early Childhood Education. Authors were used to base the theme of the training meetings, as well as to analyze the data produced, such as Horn (2004), Rinaldi (2016) and Gandini (2016). It is considered that times and spaces are diverse and unique for each child, that is, for each child's experience there is a specific time within a given space. In this way, some important points were presented to think about the organization of spaces and times, because the child experiences them in different ways, re-meaning their learning and sewing their new flaps to the old ones and thus, through the seams create something that can surprise. The discussions between the teachers and managers allowed us to understand that the organization of spaces and times needs to gain more openness in the conversations of the continuing formations so that, little by little, it can be tailored to the teaching practice. The product was set up in two ways: the first as formative meetings with teachers and managers and the second from the construction of a book produced with fabric flaps and sewn at the end of the two meetings containing the records of the discussions that took place during the formations. The result is considered extremely significant, because it made possible provocations related to the organization of spaces and times in Early Childhood Education.